1391 Unscheduled neonatal attendances. (17th August 2022) - Rodger, David; Kirolos, Sandy; Campbell, Gillian; Mitchell, Jennifer
Abstract : Aims: The easing of Covid-19 lockdown measures led to an unprecedented increase in paediatric emergency department (ED) attendances. Neonates represent a vulnerable group who can be challenging to manage in the ED due to infection risk and lack of specialised facilities. Care on the postnatal wards or review in a dedicated neonatal outpatient area, where feeding support and maternal care can be provided, may be more appropriate and have the added benefit of reducing pressure in the ED. To facilitate this, a mutually agreed pathway between ED and neonatal services is essential. We aimed to ascertain the burden of neonatal presentations to ED and create a referral pathway for unscheduled neonatal presentations ( figure 1 ). Methods: This was a retrospective observational review of babies less than 14 days of age presenting to the ED of a tertiary paediatric hospital with adjacent maternity and neonatal facilities. To account for random variation in ED presentations over consecutive weeks, attendances on the first week of four alternate months in 2020 (January, March, May, July) were included. Variables analysed included antenatal and postnatal history, presenting complaint, discharge diagnosis, and length of ED stay. The data was used to inform a referral pathway that identifies patients appropriate for discussion with the neonatal team. Results: 42 babies met the criteria over the sampled weeks, with a mean of 11 per week. Of note, this number was comparable the same time period in both 2019 and 2021. All were born at term (>37 weeks) and none had previous NNU admissions. Of the babies 61% were born to primigravida mothers. 43% were self-referrals to ED and 38% had community midwife review on the same day as attendance, with 2 being telephone reviews. Half presented between the hours of 20:00pm and 08:00am. The mean length of stay in ED was 2.2 hours. The most common discharge diagnoses were 'well baby', 'feeding problem' and 'periodic breathing' ( figure 2 ). 26% were admitted to paediatric services, of those 63% were discharged within 24 hours of admission. Conclusion: The data in this cohort reflects the fact that most neonates presenting to ED were clinically well, however, some require a period of observation prior to safe discharge. The referral pathway ( figure 1 ) was intended for babies <14 days and identifies those appropriate for discussion with the neonatal team, in particular where the main presenting problem is a feeding issue, jaundice or weight loss. In addition, it excludes any baby with possible respiratory infective symptoms that would preclude them from NNU admission. The referral pathway ( figure 1 ) allows for a conversation between ED and neonatal teams, aiming to ensure babies with routine neonatal issues are assessed in the most appropriate area, while acknowledging the need for flexibility due to out of hours neonatal staffing, cot capacity and need for observation prior to discharge.